Shelf life of chill stored pangasius (Pangasianodon hypophthalmus) fi sh fi llets: effect of vacuum and polyphosphate - Madhusudana Rao, B.; Narasimha Murthy, L.; Prasad, M. M. (Indian Journal of Fisheries, 2013)
Pangasianodon hypophthalmus, commonly known as pangasius is internationally marketed in the form of frozen fi llets. Value addition for domestic markets in the form of fi llets, fi ngers, cutlets and fi sh balls may be an alternative but the lack of proper cold chain facilities (-18 °C) in the domestic sector is an impediment to market these products. The present study was taken up to determine the shelf life of pangasius fi llets in chilled condition (<4 °C) in ice. The proximate composition showed that pangasius fi llets are a good source of easily digestible protein (17.24%). Four batches of pangasius fi sh fi llets were prepared for the experiments. The fi rst batch (CC, chilled control) of pangasius fi llets were packed individually in polythene pouches; the second batch (VC, vacuum control) vacuum packed in polythene pouches; the third batch (CT, chilled treated) soaked in chill water solution [(1% salt, 2% sodium tri polyphosphate (STPP)] for 30 min and packed in polythene pouches and the fourth batch (VT, vacuum treated) was soaked in chilled water solution containing 1% NaCl, 2% STPP for 30 min and vacuum packed in polythene pouches. All the pouches were stored under chilled condition (4 ºC) in ice. The fi llets were analysed for chemical and microbiological parameters at regular intervals viz., 0, 3, 6, 9 and 12 days of storage. The phosphate content of CT (4410 ppm) and VT (4120 ppm) fi llets at the end of 12 days of chilled storage was lower than the permissible limit of 5000 ppm. PV values were lower, both in STPP treated and in vacuum packed fi llets. Total volatile base nitrogen (TVBN) values were lower than 30 mg100 g-1 in CC, CT, VC and VT fi llets till 9 days of chilled storage and thereafter showed relatively rapid increase. The texture of treated fi llets (CT and VT) was fi rm. The colour of vacuum packed fi llets (VC and VT) was relatively darker. The aerobic plate count (APC) of STPP treated fi llets (CT and VT) was lower than the corresponding control fi llets (CC and VC). The results indicate that pangasius fi llets can be stored for a period of 9 days in chilled condition (<4ºC) and soaking the fi llets in 1%NaCl and 2% STPP chilled water would improve texture and moisture retention.